The Effectiveness of Emotion Regulation Training Based on Gross Model in Reducing Impulsivity in smokers - Mohammad Asgari; azam Matini (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2020)
The aim of this study was to determine the effect of Teaching Emotion Regulation Based on Gross Model in Reducing Impulsivity in smokers. The research method was semi-experimental and was use of the unequal control group design. For this purpose, 30 smoker students of Islamic Azad University of Hamedan were selected and randomly divided into two experimental and control groups. First, Barrett's Impulsivity Scale (1997), was performed for both groups. Then, the experimental group received a teaching emotion regulation based on Gross model for 8 sessions. But the control group did not receive any training. After completing the training, Barrett's impulsivity scale was again performed for both groups. Analysis of data using multivariate analysis of covariance (MANOVA) showed that emotional regulation training based on Gross model has a positive effect on reducing the impulsivity of smokers, & on cognitive impulsivity, motor impulsivity, non-planning impulsivity. The results showed that Grass's emotion regulation training had an effect on the impulsivity of smokers and reduced impulsivity. Since smokers are exposed to negative emotions, they are likely to be unplanned and impacted; therefore, emotional regulation training based on Grass's model can be effective in reducing the impulsivity of smokers. (p <0.01)